Some basic questions about (a) decolonizing Africa(n)-centred psychology considered. (September 2018) - Ratele, Kopano; Cornell, Josephine; Dlamini, Sipho; Helman, Rebecca; Malherbe, Nick; Titi, Neziswa
Conceptual disagreement remains rife with regard to African psychology with some scholars mistakenly equating it to, for example, ethnotheorizing and traditional healing, while others confound African psychology with Africanization and racialization. Using writing as inquiry, this article aims to clear up some of the conceptual confusion on African psychology while engaging with the issue of a decolonizing African psychology. Accordingly, questions such as 'What is the main dispute between Africa(n)-centred psychology and Euro-American-centric psychology in Africa?'; 'Does Africa(n)-centred psychology not homogenize Africans?'; 'What can be gained from imbricating decolonizing perspectives and feminist Africa(n)-centred psychology?'; and 'What would a decolonizing Africa(n)-centred community psychology look like?' are pertinent in the clarification of the conceptual confusion. Arising from an inventive dialogical and collaborative method, the aim of this article is not only to illuminate some basic misunderstandings on (a) decolonizing African psychology but also to generate further dialogue on how to work towards African psychology as situated decolonizing practice and knowledge.